Design and Construction of an Electronic Mosquito Repellant - Isaac, Kwesiga (Kabale University, 2022)
A Project Submitted to the Department Of Physics in Partial Fulfilment of the Requirements for the Award of the Degree of Bachelor of Science with Education (Physical) of Kabale University